Evaluation of recreation departments in theory and practice - Ahmet Tarık Ergüven (Journal of Education and Learning (EduLearn), 2023)
It is our source and it is irreversible. With industrialization, the time people spend at work has decreased, and their free time has increased. This has led people to look for new ways to spend their free time productively. At this point, graduates of the recreation department will have the opportunity to show the methods that will be useful for people to spend their free time efficiently in line with the education they receive. Since graduates are thought to be employed in organizations that provide leisure time services, the qualifications of graduates are important in this regard. In this study, the expectations of the employers from the graduates and the required qualifications of the graduates were investigated. One issue drawn from the results is that although each branch has specific expectations, all graduates must have certain qualifications, such as communication and constructive language skills.